Anti-Ri-associated paraneoplastic brainstem cerebellar syndrome with coexisting limbic encephalitis in a patient with mixed large cell neuroendocrine lung carcinoma. Issue 2 (February 2015) - Mitchell, Amber N.; Bakhos, Charles T.; Zimmerman, Earl A.
Abstract Paraneoplastic neurologic syndromes (PNS) can be the first manifestations of occult malignancies. If left untreated, PNS often lead to significant morbidity and mortality. Anti-Ri (anti-neuronal nuclear antibody type 2 [ANNA-2]) autoantibodies are commonly associated with breast and small cell lung cancers. Cases of anti-Ri paraneoplastic cerebellar degeneration are reported, but few describe severe nausea and coexisting limbic encephalitis as the major presenting features. We report a 75-year-old woman with medically-intractable emesis, encephalopathy, diplopia, vertigo, and gait ataxia for 3 months. Examination revealed rotary nystagmus, ocular skew deviation, limb dysmetria, and gait ataxia. After two courses of intravenous immunoglobulin, there was minimal improvement. Anti-Ri antibodies were positive in serum only. CT scan identified a 2.0 cm left lung mass, and histopathology revealed large cell neuroendocrine carcinoma with admixed adenocarcinoma non-small cell lung carcinoma (NCSLC). Though the patient achieved nearly complete clinical recovery after tumor resection, anti-Ri levels remained high at 20 months post-resection. To our knowledge this is the first report of a paraneoplastic brainstem cerebellar syndrome with coexisting limbic encephalitis involving anti-Ri positivity and associated mixed neuroendocrine/NSCLC of the lung with marked improvement after tumor resection.